2021
DOI: 10.1177/10499091211006923
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Symptomatology of Hiccups in Patients With Cancer: Using an On-Line Medical Community to Better Understand the Patient Experience

Abstract: Background: Cancer patients are at risk for hiccups, but the incidence and impact on quality of life are unclear. Methods: A survey (modified from the Functional Living Index with the inclusion of qualitative elements) was developed and launched on an 80,000-member medical social media platform, Mayo Clinic Connect https://connect.mayoclinic.org/ . Results: Among 213 respondents, 34 (16%; 95% CI: 11, 22%) reported “yes” that they had experienced hiccups with cancer therapy. Of those patients who reported hiccu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…We found that 28% had hiccups. This percentage is in keeping with what others have previously reported with chemotherapy-induced hiccups, underscores that the development of hiccups is not a rare event, but, for the first time, provides important patient-reported data on hiccups [3,4]. The finding that over one-quarter of patients reported � Other consisted primarily of lung, bladder, cervical, and testicular cancer.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found that 28% had hiccups. This percentage is in keeping with what others have previously reported with chemotherapy-induced hiccups, underscores that the development of hiccups is not a rare event, but, for the first time, provides important patient-reported data on hiccups [3,4]. The finding that over one-quarter of patients reported � Other consisted primarily of lung, bladder, cervical, and testicular cancer.…”
Section: Discussionsupporting
confidence: 89%
“…What percentage of cancer patients who receive oxaliplatin-or cisplatin-based chemotherapy experience hiccups? Previous estimates cite 15-40% of patients who receive chemotherapy develop hiccups, but this percentage might be inaccurate for at least three reasons [3,4]. First, such percentages have at times been derived from databases.…”
Section: Introductionmentioning
confidence: 99%
“…Doing so puts patients at ease to talk about hiccups post chemotherapy. Although the ratio of effort to yield with this approach might seem high, our research suggests hiccups occur in 16% of cancer patients, making hiccups a horse rather than a zebra 7…”
Section: The First Step: Assessmentmentioning
confidence: 77%
“…1 Based on our estimates and extrapolations, approximately 5% of patients with cancer not only experience hiccups but describe them as exceedingly troublesome. 2 When one considers the many thousands of patients treated for malignancies every day in the United States, this modest rate of 5%, nonetheless, translates into a sizable daily burden of suffering for many hundreds of patients with cancer—not to mention for patients with other illnesses that induce hiccups. Furthermore, some patients are at risk for serious hiccup-induced complications, such as aspiration, sleep deprivation, nutritional compromise, and even life-threatening, life-limiting events.…”
Section: Introductionmentioning
confidence: 99%